Potensi Bakteri Endofit Asal Lantana camara, Kelapa Sawit, dan Mangrove untuk Mengendalikan Meloidogyne spp. pada Tanaman Terung - Siti Zulaiha; Abdul Munif; Abdjad Asih Nawangsih (Jurnal Fitopatologi Indonesia, 2022)
Potential of the Endophytic Bacteria from Lantana camara, Palm Oil, and Mangroves to control Meloidogyne spp. on EggplantRoot knot nematodes Meloidogyne spp. is one of the important pathogens in eggplant. Root gall is very detrimental disease that can cause production reduces. This study aims to obtain endophytic bacteria from Lantana camara and evaluate them together with endophytic bacteria from oil palm roots and mangroves which have the potential to control Meloidogyne spp. and determine its effect on eggplant growth, as well as identify potential endophytic bacteria as biological control agents. The biological control agents’ potency was referred to screening results such as mortality test, volatile organic compound (SOV) and suppress test on root gall was evaluated by measuring percentage of gall reduction, root damage scale and egg package. The results showed that all endophytic bacteria isolates had the potential to mortality of Meloidogyne spp. and produce SOV as well as can suppressing the percentage of gall reduction in eggplant root and have effect to the weight and height of the plant. Isolates LCA5 and LCA13 had the potential to mortality of Meloidogyne spp. above 90% during 24 hours, and the SOV test causes mortality above 60% for 24 hours. Endophytic bacteria that have potential as biological control were identified as Dyella marensis, Stenotrophomonas rhizophilla, and Providencia vermicola.